Impact FD: An Unreliable Failure Detector Based on Process Relevance and Confidence in the System. (30th April 2018) - Rossetto, Anubis Graciela de Moraes; Geyer, Cláudio F R; Arantes, Luciana; Sens, Pierre
Abstract: This paper presents a new unreliable failure detector, called the Impact failure detector (FD), that, contrarily to the majority of traditional FDs, outputs a trust level value which expresses the degree of confidence in the system. An impact factor is assigned to each process and the trust level is equal to the sum of the impact factors of the processes not suspected of failure. Moreover, a threshold parameter defines a lower bound value for the trust level, over which the confidence in the system is ensured. In particular, we defined a flexibility property that denotes the capacity of the Impact FD to tolerate a certain margin of failures or false suspicions, i.e. its capacity of considering different sets of responses that lead the system to trusted states. The Impact FD is suitable for systems that present node redundancy, heterogeneity of nodes, clustering feature and allow a margin of failures which does not degrade the confidence in the system. The paper also includes a timer-based distributed algorithm which implements an Impact FD, as well as its proof of correctness, for systems whose links are lossy asynchronous or for those whose all (or some) links are eventually timely . Performance evaluation results, based on PlanetLab (Planetlab. http://www.planet-lab.org. 'Online. Access date: 16 September 2016') traces, confirm the degree of flexible applicability of our FD and that, due to the accepted margin of failure, both failures and false suspicions are more tolerated when compared to traditional unreliable FDs.